Effect of Three Soil Tillage Practices on Soil Organic Matter and Nutrient in Any Semi-Arid Area in Tunisia - Rezgui, Mohsen; Sebei, Abdennour; Bchini, Houcine; Bahrouni, Hassouna (Advances in Social Sciences Research Journal, 2020)
The distribution of soil organic matter (SOM), nitrogen (N), potassium (K), total calcium carbonate (CaCO3) and pH was studied in relation to three soil tillage practices: conventional (CT) using mouldboad plough followed by three crossing of off-set disc harrow, tooth harrow and seed drill, Reduced (RT) using a chisel, and no-till (NT) using direct driller and 2 plant species: Vicia faba and Durum wheat, grown in a clayey soil of the semi-arid region of Kef (North western Tunisia) during three years 2009-2011. Results showed that, under NT, Vicia faba increased SOM and N in the first fifteen centimeters by 20% and 84% respectively as compared to the CT, and reduced soil pH by 0.1 unit. Indeed, Vicia faba benefited from the residues of the Durum wheat. In contrast, CT buried the residues of the previous crop increasing the rate of SOM and N in the subsoil (30-45 cm depth). This made clear that NT, had the benefit of improving top-soil fertility and putting soil nutrients at the reach of the Vicia faba plant roots. Moreover, NT increased the concentration of K in the top-soil which helped seedlings and young plants resisting biotic and non biotic stresses imposed by the semi-arid environment.